For territorial reading of the Cerrado:: the perverse link between the production of wealth and social inequality (Élisée - Revista de Geografia da UEG, 2020)
The collective endeavor around the geographic construction of an approach to the Cerrado - and research directly involving the Cerrado in Goiás, allow two questions: what are the production of meaning of the different representations of the Cerrado? This question may be simpler: what is the political sense that comes from the representations of the Cerrado? Through an active dialogue with geographers from Goiás and outside Goiás; and also with members of the Social Movements and with all those who defend integral life and human rights, we point out that, for the critical reading of the Cerrado interpretation, there is a need to intertwine the notions of Biome and Territory. This intertwining starts from a premise: the Cerrado of Goiás is a geopolitical construction. Therefore, it is necessary, in a critical analysis, to unveil its ideologization and understand the formation of an unequal territory.
Keywords: Territorial reading of the Cerrado. Social inequality. Geopolitics. Geographic scales.